INFLUENCING FACTORS UTILIZATION PMK TAX INCENTIVE NUMBER 128 OF 2019 - Asih Machfuzhoh; Galih Fajar Muttaqin; Intan Puspanita (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
One of the MBKM programs is a certified internship program. The government supports improving the quality of graduates, both undergraduate and diploma. Apart from the MBKM Program, from a tax perspective it also provides support related to increasing graduates, by providing tax incentives to companies that have contributed to providing internship opportunities to students. This incentive is the Supertax Deduction. It is hoped that by providing this incentive, many companies will contribute to providing internship opportunities for universities. Unfortunately, this facility has not been maximized by taxpayers. This research aims to test the influence of understanding supertax deduction incentive regulations, vocational student internships, socialization and ease of supertax deduction incentives, on the implementation of supertax deduction among vocational program partners. The sample for this research is all industrial partners involved internship program in 90 industries spread across Banten Province. The research methodology stage begins with collecting data through distributing questionnaires to vocational partners, followed by data analysis. This research data is primary, the data was analyzed using validity and reliability tests and multiple linear regression tests. The results of this research found that the influence of understanding the supertax deduction incentive regulations, socialization and ease of supertax deduction incentives had an influence on the implementation of supertax deduction